Misuse of English morphology in writing among TESL students / Nur Ilyani binti Idris - Idris, Nur Ilyani (2015)
This paper studies about the misuse of English Morphology in Teaching English as a Second Language (TESL) students’ writing from KPTMKL. This study is design to find out the morphological errors in students’ writing using the Surface Strategy Taxonomy proposed by Dulay (1982). There are three objectives of the study; firstly is to identify the types of morphological errors used by TESL students in journal writing such as omission, addition, miss formation or miss ordering, secondly is to examine the most dominant type of morphological errors in journal writing, and finally to analyze the interference of the mother tongue resulting to the morphological error in students’ journal writing. The qualitative method used in this study and this is based on the journal that they have written for fourteen weeks. The researcher chose fifteen participants to participate in the study. All fifteen journals that have morphological errors have been chosen to be analyzed. The findings show that simple addition, regularization and also omission of preposition were the most common types of morphological errors made by TESL students. While, simple addition was the most dominant type of error found by the researcher. In addition, TESL students prone to use their mother tongue (Malay) and tend to translate it in English. This happens especially in writing and at the same time affect their sentence structure in the sense of they tend to omit auxiliary verb in sentences, omit noun inflection ‘-s’ for possessive nouns and also omit an article.